The Effect of Brief Meditation on Visual and Auditory Modalities of Temporal Processing - Sharma, Shiv Parshad (Thapar Institute of Engineering and Technology, 2025)
Time Perception is a phenomenon through which an individual experiences the sense of time or is aware of the passage of time. The perception of time has always been discussed among philosophers and modern cognitive scientists. The perception of time of an individual is affected by various cognitive functions like memory, attention, and executive functions. In the study, we wanted to examine whether Brief meditation training affects the different modalities of temporal processing. Using a convenience sampling method, we have recruited 61 participants, aged 18-30, from Thapar Institute of Engineering and Technology. The participants were divided into 36 participants in the Meditation group and 25 in the relaxation group. The participants were made to perform the Visual and Auditory Bisection task, which has 3 phases: Training phase, Feedback Phase, and Testing Phase. In the testing phase, there are seven different durations ranging from 200ms to 800ms with increments of 100ms that randomly appear on the white screen as a black square and neutral sound in the auditory temporal bisection task. The participants need to judge whether the presented stimulus is closer to the shorter or longer anchor duration using the “S” and “L” Keys on the Keyboard, respectively. The participants in the relaxation group were made to perform the same task with a different intervention. The participants were made to perform these bisection tasks two times: once before the meditation or relaxation training and once immediately after the intervention was given. The participants perform the visual bisection task and the auditory bisection task in a gap of one day because the brief effect of meditation/relaxation training may be reduced after one bisection task, and also to reduce the fatigue effect in an individual. The results of the current study show that in the meditation group, participants have experienced subjective expansion of time in the visual modality of temporal processing. After training, participants showed lower PSE and higher temporal processing in the Visual Bisection task. The participants 4 showed a lower level of accuracy and change in the subjective experience of time due to increased temporal sensitivity. This subjective expansion of time in a visual bisection task could be due to a higher allocation of attentional resources due to brief meditation training. In addition, we have found that participants show no difference in point subjective equality (PSE) and Difference Limen (DL) between pre- and post-training tasks. The auditory modality of temporal processing already has higher temporal processing and more automatic attention-directing capacity. The meditation training does not affect the temporal sensitivity of the participants in their auditory modality of temporal processing. In our second experiment, the participants were made to listen to relaxation music and perform the same visual and auditory temporal bisection tasks. The results show no difference in the PSE and DL between pre- and post-training tasks in both the Visual and Auditory bisection tasks. The relaxation training alone did not affect the participants' temporal processing and attentional resources. So, from our results, we can conclude that the effect of Brief Meditation training is modality-specific and does not affect the auditory modality of temporal processing.
Keywords: Time Perception; Attention; Meditation; Point of Subjective Equality; Temporal Processing; Temporal Sensitivity